PENGARUH NILAI-NILAI MULTIKULTURALISME TERHADAP PENGAMALAN NILAI KERUKUNAN SISWA KELAS X DI SMK NEGERI 5 PEKANBARU - Desy Dorasih; Hambali Hambali; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was motivated by the attitude of equality, regardless of sex, mutual respect that can instill a sense of sympathy and there is no discrimination in a learning process. The formulation of the problem in this research is How the influence of values of multiculturalism to the practice of the value of harmony of students of class X SMK Negeri 5 Pekanbaru, The purpose of this study is to know the extent to which the influence of the values of multiculturalism to value harmony students. This type of research is quantitative descrip- tive Research and Tech nik taking the sample used is random sampling. Data collection techniques in this study were conducted by questionnaire to 77 respondents. Is known use values-the value of multiculturalism contributed 54% in affecting the value of harmony.while for the other 46% is influenced by other factors. The formulation of the hypothesis was formulated that is Influence Values Against Multiculturalism practice Harmony Value Class X in SMK Negeri 5 Pekanbaru is high means that the practice of value harmony student / I claas X in SMK Negeri 5 Pekanbaru with the percentage of 56.84%. These results indicate that the influence of significance based on testing conducted in this study showed that there were significant effects characterized by F count ≥ F tables or (9.502) ≥ (0.22242). Thus, Ha is accepted while Ho is rejected which means there is influence of values of multiculturalism, or the higher the influence of values of multiculturalism then the higher the practice of harmony values owned by students of class X in SMK Negeri 5 Pekanbaru.Keywords: Value, Multiculturalism, Concord